Pertumbuhan dan Tingkat Kelangsungan Hidup Mikrofragmen Karang Montipora sp. pada Intensitas Cahaya dan Jenis Material Substrat yang Berbeda - Damanik, Gabriel Dala Bona Pangihutan; Putra, I Nyoman Giri; Widiastuti (Journal of Marine Research and Technology, 2026)
Coral reef ecosystems are susceptible to environmental changes such as temperature, salinity, sedimentation, and eutrophication, and require optimal water quality to sustain their function. Increasing pressures on coral reefs threaten their survival as well as the associated biotas. Key environmental components that support coral growth and survival include light and substrate. Light intensity influences photosynthesis, while substrate type affects coral growth. This study aimed to evaluate the growth and survival rates of the microfragmented coral Montipora sp. under different light intensity (high: 200-300 µmol photons/ms2, moderate: 150-200 µmol photons/ms2, low: 150 µmol photons/ms2) and material substrate type (cement and ceramic) for 12 weeks. Growth rate of Montipora sp. under different substrate material types were analyzed using Independent - T, whereas the growth rate under different light intensities was analysed using One-Way ANOVA. Results showed that growth decreased during weeks 0 - 2, however it is increased from weeks 3–11 across treatments. The growth rate of Montipora sp. did not differ significantly between ceramic (0.4 ± 0.03 cm²/week) and cement substrates (0.6 ± 0.05 cm²/week). Similarly, growth rates under different light intensities (150–300 µmol photons/m²/s) were not significantly different, with values of 0.3 cm²/week at high intensity and 0.5 cm²/week at medium and low intensities. Survival rates remained 100% across all treatments, regardless of substrate type or light intensity.